2018
DOI: 10.3390/s18040942
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized Bio-and Chemical-Sensors for Point-of-Care Monitoring of Chronic Kidney Diseases

Abstract: This review reports the latest achievements in point-of-care (POC) sensor technologies for the monitoring of ammonia, creatinine and urea in patients suffering of chronic kidney diseases (CKDs). Abnormal levels of these nitrogen biomarkers are found in the physiological fluids, such as blood, urine and sweat, of CKD patients. Delocalized at-home monitoring of CKD biomarkers via integration of miniaturized, portable, and low cost chemical- and bio-sensors in POC devices, is an emerging approach to improve patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 77 publications
0
36
0
Order By: Relevance
“…Additionally, another three sweat metabolites, including urea, uric acid, and creatinine, create opportunities for diagnostics of kidney disorders. The levels of sweat urea and creatinine are typically higher in patients with kidney disorders than in healthy individuals, since the failure of glomerular function [ 79 , 154 ]. As described previously, Zhang et al [ 34 ] reported a microfluidic biosensor for colorimetric analysis of urea and creatinine for POCT of kidney diseases.…”
Section: Key Analytes and Wearable Biosensing Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, another three sweat metabolites, including urea, uric acid, and creatinine, create opportunities for diagnostics of kidney disorders. The levels of sweat urea and creatinine are typically higher in patients with kidney disorders than in healthy individuals, since the failure of glomerular function [ 79 , 154 ]. As described previously, Zhang et al [ 34 ] reported a microfluidic biosensor for colorimetric analysis of urea and creatinine for POCT of kidney diseases.…”
Section: Key Analytes and Wearable Biosensing Platformsmentioning
confidence: 99%
“…For example, wearable microfluidic/electrochemical sweat biosensors are able to detect various electrolytes, such as sodium ions (Na + ) [ 14 , 61 , 63 , 64 , 65 , 66 , 67 ], potassium ions (K + ) [ 14 , 63 ], calcium ions (Ca 2+ ) [ 32 ], and ammonium (NH 4 + ) [ 68 ], multiple metabolites, such as glucose [ 14 , 37 , 69 , 70 , 71 , 72 ], lactate [ 14 , 21 , 63 , 73 , 74 , 75 ], several heavy metal species, such as zinc, iron, copper, and magnesium [ 61 , 76 ], and drug contents, such as Levodopa [ 77 ] (more sweat analytes can be found in Section 5.1 and Table 1 ). As such, sweat contains a wealth of physiologically relevant information [ 41 , 43 , 45 ] that can reflect hydration [ 21 , 27 , 33 , 74 ], electrolyte balance [ 63 ], exercise intensity [ 78 ], renal function [ 34 , 79 ], etc. For diagnostic use, wearable sweat biosensors are used to diagnose cystic fibrosis (CF), liver diseases, kidney disorders, as well as to monitor stress levels by measuring the cortisol concentrations in sweat [ 34 , 43 ,…”
Section: Introductionmentioning
confidence: 99%
“…Antonio tricoli and Giovanni neri have contributed to the current innovations and achievements in technological improvement of sensors in the healthcare sector for monitoring patients with chronic kidney disease and to measure the rate of ammonia, creatinine and urea. [2] They used Stat sensor to detect creatinine electrochemically. The sensors are highly useful in detecting the parameters but accuracy fails during diagnosis.…”
Section: Paper Surveymentioning
confidence: 99%
“…Point-of-care (POC) application for monitoring of breath ammonia (BA) in hemodialysis (HD) patients have emerged as a promising non-invasive health monitoring approach. [1][2][3] In this context, many organic gas sensors including our prior works have been reported for BA detection. 4,5 However, one of the major challenges for its integration with affordable household POC application is to achieve stable performance for accuracy and high operational current at low voltage for low-cost read-out circuitry.…”
Section: Introductionmentioning
confidence: 99%